UTILIZATION OF RICE STRAW WASTE INTO BROOMS AND DUSTER IN LAMBAET VILLAGE, KUTA BARO DISTRICT, ACEH BESAR REGENCY: PEMANFAATAN LIMBAH JERAMI PADI MENJADI SAPU DAN KEMOCENG DI DESA LAMBAET KECAMATAN KUTA BAROKABUPATEN ACEH BESAR - Endiyani; Sri Agustina; Mulla Kemalawaty; Umar HA; Yusran Akbar (PT. ROCE WISDOM ACEH, 2024)
Rice waste is the remnants of the rice farming process produced during rice production. Straw is agricultural waste from the remaining rice harvest that has not been maximally utilized and the amount is quite large during the rice harvest period. This community service activity aims to socialize to the community so that the community is able to increase knowledge and skills through the utilization of waste in the form of rice straw as raw material which can then be processed into handicrafts in the form of brooms and duster in Lambaet Village, Kuta Baro District, Aceh Besar Regency. The people of Lambaet Village are very interested and enthusiastic about the socialization of the utilization of straw waste into more useful products, so that they can optimize the utilization of straw waste in the village. The result of this community service activity is that the community has understood and known the processing of straw waste and has the creativity in making various kinds of handicrafts from straw, not only can it be used as a basic material for making brooms and duster but the community can also form creations - handicraft creations in other forms. The hope is that the emergence of community creativity in processing straw waste can increase family income for the community, in addition to minimizing air pollution conditions due to burned straw waste